Conducting research about sensitive subjects: The case of homeless youth - Koller, Silvia Helena; Universidade Federal do Rio Grande do Sul (2011)
Hay interés creciente e importancia en los desafíos logísticos y éticos de la dirección de una investigación con poblaciones en situación de vulnerabilidad, incluso los denominados sin hogar y There is growing interest and importance in addressing the logistical and ethical challenges of conducting research with disenfranchised populations, including homeless and working street youth. Drawing upon established international standards on human rights, we review legal and ethical codes for research on disenfranchised populations established by national and international research and professional organizations. Then we explore how university-based researchers can apply these standards to children and adolescents growing up in situations characterized by physical and psychological neglect, lack of adult supervision, limited protection from local law enforcement, and drug use and violence. We reflect upon on our experiences in conducting research with vulnerable Brazilian youth to illustrate the challenges of implementing ethical guidelines in real-world situations and propose possible solutions to ethical dilemmas encountered in the field.